Bringing the Stages Back in: Social Network Ties and Start-up firms' Access to Venture Capital in China - Wang, Yanbo (Strategic entrepreneurship journal, 2016)
Research summary Social networks are believed to help start‐ups access venture capital (VC). However, the causal mechanisms remain unclear because social ties probably influence both a start‐up's likelihood of being screened for evaluation and its likelihood of being funded. Whereas prior studies conceptualize venture financing as a single‐moment event, in this article, it is theorized as a dynamic multistage process in which a screening decision precedes a funding decision. Failure to address the selection effects at each stage could lead to biased findings regarding how social ties confer advantage in venture financing. This study uses a hand‐collected dataset from China to empirically examine these arguments. Managerial summary Social networks are believed to help start‐ups access venture capital. However, it is unclear whether this is because social ties help venture capitalists (VCs) and start‐ups overcome the problems of information asymmetry and behavioral opportunism in early‐stage financing or whether VCs are more likely to become aware of investment opportunities embedded within social networks. This study divides VC decision making into two stages: awareness generation and venture evaluation. This study finds that socially connected start‐ups have cumulative advantages in the access to venture capital, but this advantage mainly arises in the early stage where information embedded in social ties helps reduce investors’ search costs in deal screening. In contrast, social ties are a secondary consideration in the subsequent stage of VC funding decisions Copyright © 2016 Strategic Management Society.